Scanning tunneling microscopy (STM) and scanning electron microscopy (SEM) of electrodispersed gold electrodes - Gómez, J. (1988)
Images of large active surface (electrodispersed) gold electrodes obtained by electroreduction of an oxide layer grown by applying a fast periodic square wave potential to polycrystalline specimens, have been obtained by STM and SEM. For the first time a correlation of imaging data of both microscopes can be established which allows one to find different structural details of these electrodes. The roughening increase produced by the electrochemical activation is explained tentatively through a generalized structural model consisting of an overlayer of sticking spheres of about 10 nm average diameter leaving inner interconnected channels of nearly the same average diameter and penetrating in the overlayer structure. The size of the spherical units is comparable to that of metal clusters involving the optimal ratio of surface to bulk atoms associated with the greatest catalytic activity.